The Neoliberal State, Recognition and Indigenous Rights New paternalism to new imaginings - Howard-Wagner, Deirdre; Bargh, Maria; Altamirano-Jiménez, Isabel (ANU Press, 2018)
The impact of neoliberal governance on indigenous peoples in liberal settler states may be both enabling and constraining. This book is distinctive in drawing comparisons between three such states-Australia, Canada and New Zealand. In a series of empirically grounded, interpretive micro-studies, it draws out a shared policy coherence, but also exposes idiosyncrasies in the operational dynamics of neoliberal governance both within each state and between them. Read together as a collection, these studies broaden the debate about and the analysis of contemporary government policy.The individual studies reveal the forms of actually existing neoliberalism that are variegated by historical, geographical and legal contexts and complex state arrangements. At the same time, they present examples of a more nuanced agential, bottom-up indigenous governmentality. Focusing on intense and complex matters of social policy rather than on resource development and land rights, they demonstrate how indigenous actors engage in trying to govern various fields of activity by acting on the conduct and contexts of everyday neoliberal life, and also on the conduct of state and corporate actors.